Consumer motivation for product disposal and its role in acquiring products for reuse. Issue 7 (26th June 2019) - Simpson, Dayna; Power, Damien; Riach, Kathleen; Tsarenko, Yelena
Abstract: Product reuse is most profitable where manufacturers acquire used products in the best possible condition—near new and with little wear and tear. This requires consumers, however, to dispose of products that still work and may still be in use. Prior scholarship on acquiring consumer products for reuse focuses on consumer "returns"—products consumers find fault with, or bought in error. These, however, are a fraction of all products sold to consumers and available for reuse. Importantly, returns are motivated by a different set of factors, than product "disposal." We explore how psychological ownership influences consumer disposal of reusable products. Across three studies of Australian consumers, we found two psychological tendencies (attachment and frugality) increased product retention. We also found, that infrequent product use, and emotional reward, could weaken ownership and encourage disposal of products that are attractive for reuse. To our knowledge, no behavioral studies in the product acquisition literature deal with consumers before or during product disposal. We highlight a role for consumers in product acquisition, as well as contribute to the consumer psychology and mental accounting literature, and identify significant opportunity for manufacturers to leverage consumers' psychological tendencies to improve the collection of reusable products.